Transition properties of a2Σ–, b2Δ, c2Π, d2Π, and e2Σ+ electronic states of aluminum silicon radical. (September 2021) - Wu, Min; Zhu, Zunlue
Highlights: Lifetime is approximately 88.7 – 175.6 µs for the e 2 Σ + 1/2 state. d 2 Π1/2 – a 2 Σ – 1/2 and d 2 Π3/2 – a 2 Σ – 1/2 transitions are the strongest. Lifetimes are 29.3 – 40.4 and 21.2 – 30.1 µs for the d 2 Π1/2 and d 2 Π3/2 states, respectively. Lifetimes are 4.8 – 679.5 and 2.2 – 431 ms for the c 2 Π1/2 and c 2 Π3/2 states, respectively. d 2 Π3/2 – b 2 Δ3/2, 5/2, c 2 Π3/2, e 2 Σ + 1/2 – c 2 Π1/2, 3/2, and d 2 Π1/2 – b 2 Δ3/2, c 2 Π1/2 transitions are strong. Abstract: Detecting aluminum silicon can yield useful information concerning the depletion of silicon and aluminum and their recycling in astrophysical sources. In addition, such detection can be helpful for understanding gas–phase aluminum and silicon chemistry in the interstellar/circumstellar atmosphere. However, only a few transition properties of this radical have been reported. Therefore, the potential energy curves of several lowest–lying doublet states and the transition dipole moments between them were calculated using the icMRCI approach. Core–valence correlation correction, scalar relativistic correction, and spin–orbit coupling effect were included to improve the accuracy of transition properties. The radiative lifetimes of the first 16 levels were approximately 4.8 – 679.5 ms for the c 2 Π1/2 state, 2.2 – 431 ms for the c 2 Π3/2 state, 29.3 – 40.4 µs for the d 2 Π1/2 state, 21.2 – 30.1 µs for the d 2 Π3/2 state, and 88.7 – 175.6 µs for the e 2 Σ + 1/2 state. The spontaneous emissions from the c 2 Π1/2 and c 2 Π3/2 states to the a 2 Σ – 1/2, b 2 Δ3/2, and b 2 Δ5/2 states and those from the e 2 Σ + 1/2 state to the d 2 Π1/2 and d 2 Π3/2 states were located in the radio–frequency region. The d 2 Π1/2 – a 2 Σ – 1/2 and d 2 Π3/2 – a 2 Σ – 1/2 transitions were the strongest, followed by d 2 Π1/2 – b 2 Δ3/2, d 2 Π3/2 – b 2 Δ3/2, d 2 Π3/2 – b 2 Δ5/2, d 2 Π1/2 – c 2 Π1/2, d 2 Π3/2 – c 2 Π3/2, e 2 Σ + 1/2 – c 2 Π1/2, and e 2 Σ + 1/2 – c 2 Π3/2 transitions. The spontaneous emissions from these systems were located in the infrared region. The variation in the radiative lifetime of a level υ versus the rotational quantum number J was investigated for the d 2 Π1/2, d 2 Π3/2, and e 2 Σ + 1/2 states. Graphical abstract: The radiative lifetimes of the first 16 vibrational levels were roughly 4.8 – 679.5 ms for the c 2 Π1/2 state, 2.2 – 431 ms for the c 2 Π3/2 state, 29.3 – 40.4 µs for the d 2 Π1/2 state, 21.2 – 30.1 µs for the d 2 Π3/2 state, and 88.7 – 175.6 µs for the e 2 Σ + 1/2 state. The spontaneous emissions from the c 2 Π1/2 and c 2 Π3/2 states to the a 2 Σ – 1/2, b 2 Δ3/2, and b 2 Δ5/2 states and those from the e 2 Σ + 1/2 state to the d 2 Π1/2 and d 2 Π3/2 states are distributed in the radio–frequency region. The emissions from the d 2 Π1/2 – a 2 Σ – 1/2 and d 2 Π3/2 – a 2 Σ – 1/2 systems are the strongest, followed by d 2 Π1/2 – b 2 Δ3/2, d 2 Π3/2 – b 2 Δ3/2, d 2 Π3/2 – b 2 Δ5/2, d 2 Π1/2 – c 2 Π1/2, d 2 Π3/2 – c 2 Π3/2, e 2 Σ + 1/2 – c 2 Π1/2, and e 2 Σ + 1/2 – c 2 Π3/2 transitions. The spontaneous emissions from these systems are located in the IR region. Image, graphical abstract